2017
DOI: 10.1016/j.ejrad.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer in patients with chronic calcifying pancreatitis: Computed tomography findings – a retrospective analysis of 48 patients

Abstract: The presence of a pancreatic mass in a patient with CCP is suggestive of malignancy, especially when few pancreatic calcifications are observed (that are pushed aside by the tumor) and when the tumor causes dilation of the common bile duct and main pancreatic duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…“Cyst wall” indicates calcification that was found beside the cyst, and “septum” indicates calcification that was present in the cyst bulkhead. A central calcified scar consisted of calcified septations radiating outwards with a sunburst or stellate appearance called as stellate central calcifications [ 6 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…“Cyst wall” indicates calcification that was found beside the cyst, and “septum” indicates calcification that was present in the cyst bulkhead. A central calcified scar consisted of calcified septations radiating outwards with a sunburst or stellate appearance called as stellate central calcifications [ 6 , 8 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancies between the three readers’ interpretations were submitted to an imaging seminar, which was led by a senior radiologist (Weimin Chai) with more than 25 years of experience in this field, to resolve the discrepancies by consensus. The radiologists were both blinded to the pathology results and the clinical outcomes [ 8 ]. All discussion and results were recorded by the junior radiologist and approved by the team members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study analyzed discriminatory signs on CT for patients with chronic calcifying pancreatitis and eventually developed PC. It was concluded that a hypodense mass at diagnosis is a predictive factor ( 39 ). As mentioned above, combinations of CT modalities have improved its efficacy to a large extent.…”
Section: Detection Methodsmentioning
confidence: 99%
“…Calcification of pancreatic adenocarcinoma is reported when it occurs in the background of chronic calcific pancreatitis (CCP). [1] In the absence of CCP, calcification in pancreatic adenocarcinoma is very uncommon. Calcification is more commonly seen in benign pancreatic masses such as solid pseudopapillary epithelial neoplasm, serous cystadenoma, and mucinous cystic neoplasm.…”
Section: Review Of Literaturementioning
confidence: 99%